Public crises and personal threat - Breakwell, Glynis M.; Wright, Daniel B. (Thousand Oaks, California Sage Publishing, 2024)
With an emphasis on the practical, this book explains how people react to different sorts of crises, whether they be economic, environmental, health or war, and how we can better support the public, our families, and ourselves in future crises. The book interrogates how public crises are individualised, thought about, emotionally felt, and also mistrusted, all with a view to helping us understand some of the most difficult times we endure. Ideal for applied psychology students, public planning authorities and those specialising in crisis management this book will help us all to better understand the time we live in.
Chapter 1: Public crisis? What crisis? -- Chapter 2: Public crises are individualized -- Chapter 3: Personal threat and thinking -- Chapter 4: Emotions: public and personal -- Chapter 5: Habits and habituation in public crises -- Chapter 6: Attitudes, beliefs and values -- Chapter 7: Social support during public crises -- Chapter 8: Group dynamics in public crises -- Chapter 9: Crises and trust -- Chapter 10: Identity resilience and personal threat -- Chapter 11: Beyond risk, post-catastrophe threat -- Chapter 12: Nexus of crisis reactions -- Appendix 1: Identity Resilience Index (IRI) -- Appendix 2: UNLV case study -- References -- Index.
Includes bibliographical references and index
Keywords: Disasters -- Psychological aspects